Breach of Contract in Gold Pawn Agreement Based on Rahn Contract: Legal and Sharia Analysis at Pegadaian Syariah Setia Budi Medan - Siregar, Fitri Yanni Dewi; Syaputra, Muhammad Yusrizal Adi; Sitorus, Nanang Tomi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study discusses the legal aspects of default in gold pawn agreements (rahn) at Pegadaian Syariah, Setia Budi Branch, Medan. Rahn is a pawn agreement made based on sharia principles, where customers hand over goods, such as gold bars or jewelry, as collateral for debt. In practice, default often occurs, namely the inability or negligence of customers to fulfill obligations, such as delays or failure to pay loans. This gold rahn agreement is regulated in the Compilation of Sharia Economic Law and DSN-MUI Fatwa No: 25 / DSN-MUI / III / 2002 and No: 26 / DSN-MUI / III / 2002. This study uses a normative-empirical juridical method with field interview techniques. The results of the study show that customers are charged a maintenance fee every 10 days. If there is a default, the pawnshop provides an extension of time and a warning letter. If the obligation is still not fulfilled, the collateral will be auctioned according to sharia principles. Settlement of default is carried out through applicable procedures by prioritizing deliberation and negotiation, reflecting the principles of justice and welfare in Islamic economic law, and protecting the rights and obligations of both parties.